TINJAUAN PSIKOLOGI SASTRA TERHADAP TOKOH UTAMA NOVEL REMBULAN TENGGELAM DI WAJAHMU KARYA TERE LIYE - Ratih Rahayu (TELAGA BAHASA, 2017)
This paper described the main character of the novel Rembulan Tenggelam Di Wajahmu (The Moon Drowning In Your Face/RTDW) Tere Liye works of literature, especially in terms of the psychology of Sigmund Freud's theory of psychoanalysis. The main character in this novel is Ray or Rehan Rejana. Stories in RTDW inner turmoil dominated by the main character. The main character of this novel narrated given the  pportunity to travel about his past in order to answer five questions in his life. At the beginning, Ray's id appears dominant and looks incapable of being offset by his ego and superego. There are times when Ray's id appears and becomes dominant. There are times when Ray can not accept reality and feel God is not being fair to him and likes to snatch the happiness of good people. Behind all forms of protest to God, the main character superego of RTDW is still present especially when looking at the moon. It is said that Ray was given a chance five days before his death to control the dominance of his id so that finally id, ego, and superego him go hand in hand.